Assessing Pre-service Mathematics Education Teachers Deductive Reasoning via Proof Writing in Basic Geometry: The Power of SOLO Taxonomy - Gagani, Ray Ferdinand (Jurnal Pendidikan Progresif, 2023)
Assessing Pre-service Mathematics Education Teachers Deductive Reasoning via Proof Writing in Basic Geometry: The Power of SOLO Taxonomy. Objectives: This study characterizes the developmental patterns of deductive reasoning via proof-writing of pre-service mathematics education teachers using the Structure of the Observed Learning Outcome (SOLO) taxonomy. Methods: One hundred three pre-service teachers were given twelve items involving basic concepts of plane geometry to assess. An in-depth analysis of their proof was done and they were grouped through a two-step clustering technique. Findings: Four compatible levels of developmental pattern to the SOLO level were detected. At level 0, students do not know how to establish proof. At level 1, students provided a single or few valid idea/s. Students demonstrating level 2 thinking provided many true ideas. However, the proofs are unclear and illogical. Level 3 students' proof is precisely logical. Conclusion: A trend of difficulty and success characterizes their deductive reasoning and indicates that those who were not successful in a task have superficial conceptual geometry knowledge. The research concluded that the SOLO taxonomy is a precise framework for conceptual knowledge assessment and that knowledge indeed has structure. The use of the SOLO taxonomy for assessment activity is recommended. Keywords: assessment, deductive reasoning, proof writing, solo taxonomy.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202307